2019
DOI: 10.3390/ani9121120
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Different Dietary Methane Mitigation Strategies

Abstract: Simple Summary: Dietary methane mitigation strategies do not necessarily make food production from ruminants more energy-efficient, but reducing methane (CH 4 ) in the atmosphere immediately slows down global warming, helping to keep it within 2 • C above the pre-industrial baseline. There is no single most efficient strategy for mitigating enteric CH 4 production from domestic ruminants on forage-based diets. This study assessed a wide variety of dietary CH 4 mitigation strategies in the laboratory, to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 41 publications
2
55
0
Order By: Relevance
“…The greatest CH 4 mitigation potential was observed for the red seaweed A. taxiformis with almost complete inhibition in vitro with inclusion levels up to 16.7% of the organic matter (OM). A. taxiformis was highly effective in decreasing the production of CH 4 with a reduction of 99% at doses as low as 2% OM [ 45 , 46 , 47 , 48 ]. Machado et al [ 49 ] identified that bromoform was the main bioactive in A. taxiformis that promotes anti-methanogenic activity in in vitro studies.…”
Section: Overview Of In Vitro Studies Which Used Seaweeds For Feedmentioning
confidence: 99%
“…The greatest CH 4 mitigation potential was observed for the red seaweed A. taxiformis with almost complete inhibition in vitro with inclusion levels up to 16.7% of the organic matter (OM). A. taxiformis was highly effective in decreasing the production of CH 4 with a reduction of 99% at doses as low as 2% OM [ 45 , 46 , 47 , 48 ]. Machado et al [ 49 ] identified that bromoform was the main bioactive in A. taxiformis that promotes anti-methanogenic activity in in vitro studies.…”
Section: Overview Of In Vitro Studies Which Used Seaweeds For Feedmentioning
confidence: 99%
“…Improvement of forage efficiency and reduction of CH 4 emissions is of high importance to benefit the global eco-environment [12,13]. Based on the model of Moss et al [22], the C333A and CLJ3 stover diets would generate lower CH 4 emissions than the control, and CLJ1 and CLJ2 stover diets, due to differences in total VFA concentration and proportions of individual VFA.…”
Section: Predicted Ch 4 Emissionmentioning
confidence: 99%
“…Methane (CH 4 ) emission by ruminants is a significant contributing factor to the emerging global warming phenomenon [11][12][13]. In addition, enteric CH 4 formed by the fermented feed in the gastrointestinal tract of ruminant represents a loss of approximately 2-12% of gross energy (GE) intake [11].…”
Section: Introductionmentioning
confidence: 99%
“…Model calibration was performed using experimental data from an in vitro study assessing the dose-response impact of A. taxiformis on fermentation and methane production (Chagas et al ., 2019). In such a study, in vitro fermentation was carried out with rumen inoculum from two lactating Swedish Red cows.…”
Section: Methodsmentioning
confidence: 99%
“…Then, we used the generated files by IDEAS to look for global optimal solutions using the Matlab optimization toolbox MEIGO (Egea et al, 2014) that implements the enhanced scatter search method developed by (Egea et al, 2010) for global optimization. We reduced substantially the number of parameters to be estimated by setting most of the model parameters to the values reported in the original model implementation and using the information obtained from the in vitro study (Chagas et al, 2019). For example, the hydrolysis rate constant for NDF was obtained from (Chagas et al, 2019) whereas the hydrolysis rate constants of NSC ( hydr,nsc ) and proteins ( hydr,pro ) were included in the parameter estimation problem.…”
Section: Mathematical Modellingmentioning
confidence: 99%